Characteristics of Water-soluble Inorganic Ions in Aerosol and Precipitation and their Scavenging Ratios in an Urban Environment in Southwest China - Chuanjie Lin; Tingting Huo; Fumo Yang; Bin Wang; Yang Chen; Huanbo Wang (Aerosol and Air Quality Research)
Abstract Daily fine particulate matter (PM2.5) and precipitation samples were collected simultaneously at an urban site in southwest China in four segregated months in 2015 for measuring major water-soluble inorganic ions (WSIIs). Online hourly concentrations of PM10 and PM2.5 were also monitored, which showed annual mean concentrations of 67.8 and 41.6 µg m−3, respectively. PM2.5 showed the highest concentration in winter and lowest in summer. The annual mean concentration of the total WSIIs was 20.3 µg m−3, accounting for about 48.7% of PM2.5. Among the total WSIIs in ambient PM2.5, SO42− was the predominant component (49.7%), followed by NH4 + (24.1%) and NO3 − (21.4%). NH4 + and SO4 2− were the two most abundant ions in precipitation, followed by Ca2+ and NO3 −. Seasonal patterns of the major inorganic ions in precipitation were similar to those in PM2.5, with the highest concentration in winter and lowest in summer. The mean scavenging ratios were 454, 445, 364, 456, and 394 for SO4 2−, NO3 −, NH4 +, Cl−, and K+, and 116, 353, and 18 for gas SO2, HNO3, and NH3, respectively. The higher scavenging ratios of particulate ions than their gaseous precursors suggest the higher contributions of particles than gases to the total wet deposition.